Adoption of internet-based technologies in accounting: banking professionals’ perception - Abeygunasekera, A.W.J.C. (International Journal of Accounting & Business Finance, 2022)
Internet-based technologies such as big data, cloud computing, artificial intelligence, Internet of things, robotic process automation, blockchain, etc. influence the traditional accountants’ role and the accounting process despite their limited adoption within the accounting field. Why there is a minimal adoption of these technologies in accounting is less investigated. Therefore, this study endeavoured to identify the internet-based technologies that are used in the Sri Lankan banking sector, and identify the perceptions of the banking professionals on the underlying reasons for the limited adoption of internet-based technologies in accounting. Seventeen online interviews were conducted in two large licensed commercial banks, and data were analyzed inductively; the results are discussed, using the process of institutionalization by Tolbert and Zucker (1996) and the Technology acceptance model by Davis (1989). Robotic process automation (RPA), data analytics, artificial intelligence, and cloud computing were used at the banks at varying levels. Lack of technical knowledge and experience in using technology among accounting professionals; fear/reluctance in adopting advanced IT solutions; feeling of undue influence from IT staff; and the already institutionalized accounting practices resulted in lack of adoption. These technologies are still at the stage of pre-institutionalization, and for them to reach full institutionalization stage, improving the current levels of IT skills of accounting professionals; incorporating IT skills into their skill set; attempts for more rationalization/theorizing; facilitating the visualization of positive outcomes; increasing interest group advocacy; and an increase in the perceived usefulness and ease of use among staff is necessary. This study’s findings enable the promotion of internet-based technologies within banks and open new avenues for research.
Keywords: Accounting; Artificial Intelligence; Banking; Cloud Computing; Data Analytics; Robotic Process Automation